Meretas Jejak Sufisme Di Nusantara - Firdaus, Firdaus (AL-ADYAN, 2018)
Sufism that came and flourished on the archipelago was a saga that had been first formulated by the Sufis in the Middle East. The Sufis who spread the teachings of Sufism in the archipelago lived to adapt to the needs and desires of the people. The Sufis had come from abroad to preach in the archipelago and some of the area's sons studied directly in the Middle East and returned to their homeland to further their teachings. History of Sufism in Indonesia, Aceh occupies the first and strategic position, as it will eventually color the development of Sufism in the archipelago as a whole. Searching for this stream in the archipelago does not detract from the influence of those who study in the Middle East. Among the pioneers in the development of the Sufism flow in the archipelago, as mentioned in some of the literature are: Hamzah Fansuri, Syamsudin Sumatrani, Nuruddin al-Raniri Nuruddin Ar Raniri (died 1658 AD), Abdur Rauf As Sinkili (1615-1616 AD), Muhammad Yusuf Al magazine (1629-1699 M). Abdus Shamad al Palimbani. Sufis or Sufis from the beginning to Indonesia introduced the teachings of Sufism as well as various polemics that took place and prolonged it, but it was not the subject of public debate.